Creativity Profile of Students in Constructing Mathematics Learning Media - Hidayati, Wiwin Sri; Tristanti, Lia Budi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Students must be equipped with creativity as a 21st century skill. The research objective was to obtain a profile of student creativity in constructing learning media. The method used is observation and in-depth interviews. The researcher is the main instrument and observation guide and interview guide as a supporting instrument. The research subject was one of the students of the mathematics education study program taking the mathematics learning media course. The results of student creativity research, namely the subject of creating new ideas in constructing different mathematics teaching aids, using the basic concepts of multiplication and division of positive integer operations that are formed on boards and there is a touch of technology in the form of lights and barcodes. Subjects apply creative ideas as real contributions in the form of the KoKagi Ke Wort demonstration tool. The creative idea is evident in the use of lights and barcodes that can be copied using a smartphone, so that learning videos and material on prime numbers can be displayed through the LCD projector. Learning videos and practice questions for studying at home via can also be accessed via the link from the barcode.